Risk-Management of Investment Projects in Implementation of Objects of Real Economy - MILOVIDOVA, Yana D. (Journal of Advanced Research in Law and Economics; Vol 10 No 4 (2019): JARLE Vol X Issue 4(42) Summer 2019, 2019)
Risk management in financial operations is based on a diverse structure and mobility of the portfolio that allow for a structural change of a project - namely, achieving synergies in the formation of the investment portfolios. However, financial operations do not always correlate with the stock exchange rules or other covenants. This provides important evidence for the restructuring purposes of the investment portfolio. In this regard, forecasting and the development of the toolkit of the risk management may be implemented only under conditions of the real object of the economy. The idea that objects of the real economy carry not only the risk of loss of the investment but also potential a technical damage is deemed to be a scientific novelty. As a place of technical damage in the system of the risk-management, it is considered to be a possible loss for the investor not only within a separate project but also throughout the whole project. In this regard, the author has carried out significant calculations according to her own methodology based on the implementation of a project of the real economy. Construction of the risk management system in an enterprise is a persistent rigorous process that requires a tremendous amount of financial, material and human resources. The practical significance of the study is defined by the need for a detailed definition of the risk-management’s practical use and qualities applied to the investment portfolio in the implementation of objects of the real economy, which explains the relevance of the study under consideration.